2021
DOI: 10.1136/bmjopen-2020-044157
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in type and occurrence of adverse reactions to opioid analgesics: a retrospective cohort study

Abstract: ObjectivesSex as a biological variable affects response to opioids. However, few reports describe the prevalence of specific adverse reactions to commonly prescribed opioids in men and women separately. A large cohort was used to investigate sex differences in type and occurrence of adverse reactions associated with use of codeine, tramadol, oxycodone and hydrocodone.DesignRetrospective cohort study.SettingParticipants in the Right Drug, Right Dose, Right Time (RIGHT) Study.ParticipantsThe medical records of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
2
11
0
1
Order By: Relevance
“…On the whole, a higher number of AEs was observed for females except for the sexual area, in line with previous evidence [ 3 , 20 , 47 , 48 ]. In general, women were more likely to report gastrointestinal and nervous systems issues compared with men, which can lead to the higher female hospital frequentation observed in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the whole, a higher number of AEs was observed for females except for the sexual area, in line with previous evidence [ 3 , 20 , 47 , 48 ]. In general, women were more likely to report gastrointestinal and nervous systems issues compared with men, which can lead to the higher female hospital frequentation observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…OXN and TAP are two new-generation opioids, which apparently show a better safety profile and greater effectiveness compared to Other Prescribed Opioids (OPO) in real-world pain units (PU) [ 18 , 19 ]. There are some data related to the sex differences in OXN [ 8 , 20 ] mostly due to gastrointestinal AEs [ 8 , 20 ] but not as much as with TAP or comparing both opioids.…”
Section: Introductionmentioning
confidence: 99%
“…The worse analgesic tolerability in females -related to gastrointestinal and nervous systems- and 10% more emergency department visits, falls in line with previously published scientific literature [ 34 , 35 , 36 , 37 ]. However, in spite of male cases having the lowest number of AEs, they arose the highest ADRs notification.…”
Section: Discussionsupporting
confidence: 88%
“…In the case of women, adverse reactions following antibiotic administration were most frequently reported, for example, after using ceftriaxone and for anti-tuberculosis drugs [14]. In a retrospective cohort study evaluating the incidence of adverse reactions after analgesics, women reported such symptoms almost twice as often as men [15].…”
Section: Discussionmentioning
confidence: 99%